2021
DOI: 10.1371/journal.pntd.0009610
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes and phenotypes of G6PD deficiency among Indonesian females across diagnostic thresholds of G6PD activity guiding safe primaquine therapy of latent malaria

Abstract: Background Plasmodium vivax occurs as a latent infection of liver and a patent infection of red blood cells. Radical cure requires both blood schizontocidal and hypnozoitocidal chemotherapies. The hypnozoitocidal therapies available are primaquine and tafenoquine, 8-aminoquinoline drugs that can provoke threatening acute hemolytic anemia in patients having an X-linked G6PD-deficiency. Heterozygous females may screen as G6PD-normal prior to radical cure and go on to experience hemolytic crisis. Methods & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The results from this study identified (i) confirmed hemizygous males with G6PD activity as low as 68% and (ii) confirmed homozygous females with G6PD activity below 80%. These observations are supported by a recent large US based study correlating percent activity against reference range [ 39 ] and a study with females in Indonesia [ 40 ]. Establishing a performance threshold for intermediates at 80% G6PD activity will result in (i) a significant lowering of the positive predictive power of the test for G6PD intermediate cases due to the lower AUC and (ii) a significantly higher proportion of females with homozygous G6PD normal alleles included in the intermediate group, if they have equivalent activity distributions to hemizygous normal males.…”
Section: Discussionsupporting
confidence: 63%
“…The results from this study identified (i) confirmed hemizygous males with G6PD activity as low as 68% and (ii) confirmed homozygous females with G6PD activity below 80%. These observations are supported by a recent large US based study correlating percent activity against reference range [ 39 ] and a study with females in Indonesia [ 40 ]. Establishing a performance threshold for intermediates at 80% G6PD activity will result in (i) a significant lowering of the positive predictive power of the test for G6PD intermediate cases due to the lower AUC and (ii) a significantly higher proportion of females with homozygous G6PD normal alleles included in the intermediate group, if they have equivalent activity distributions to hemizygous normal males.…”
Section: Discussionsupporting
confidence: 63%
“…Glucose-6-phosphate dehydrogenase deficiency is one of the most common human enzyme deficiencies, affecting approximately 500 million people worldwide or 6.3% of the estimated 7.9 billion persons alive ( Cappellini and Fiorelli, 2008 ; Frank, 2005 ; Louicharoen et al., 2009 ; Luzzatto et al., 2020 ; Nkhoma et al., 2009 ; Satyagraha et al., 2021 ; WHO, 2019 ). G6PD deficiency, an X-linked recessive condition, makes RBCs more vulnerable to oxidative stress ( Cappellini and Fiorelli, 2008 ; Frank, 2005 ; Louicharoen et al., 2009 ; Satyagraha et al., 2021 ; WHO, 2019 ). G6PD is the rate-limiting enzyme of the pentose phosphate pathway, which produces NADPH that, in turn, maintains glutathione in a reduced state, thereby protecting cells from reactive oxygen species ( Ravikumar and Greenfield, 2020 ).…”
Section: Common Human Enzyme Deficienciesmentioning
confidence: 99%
“…Most hemi- and homozygous individuals have G6PD activities below 30% (G6PD deficient) or above 70% to 80% of normal activity (G6PD normal) [ 36 ]. Conversely heterozygous females have enzyme activities ranging from close to 0% to almost normal activities, with activities of the majority of heterozygous females clustering around the 50% mark [ 37 ].…”
Section: G6pd Deficiencymentioning
confidence: 99%